Upaya Pembuktian Dakwaan Penuntut Umum Berbentuk Kombinasi Dan Pertimbangan Hakim dalam Memutus Perkara Tindak Pidana Perdagangan Orang - Rezha Nugroho (Sebelas Maret University, 2019)
This law research aimed to answer the following problems. Firstly, whether the attempt of authentication the Public Prosecutor’s indictment in the form of crime in human traffcking and worker recruitment combination has used legal evidence according to Article 184 of Criminal Procedural Law (KUHAP). Secondly, whether the judge’s rationale in deciding the Defendant guilty has been consistent with primary indictment and in sentencing cumulative punishment in human traffcking crime has been consistent with Article 183 jo Article 193 of Criminal Procedural Law (KUHAP). The result of the research showed that frstly, the Public Prosecutor’s indictment use combined indictment by combining alternative and subsidiary indictments. Public prosecutor, based on the indictment document, had fled evidence including Witness statement, and Defendant’s statement and information, before the court. It has fulflled the provision of Article 184 clause (1) a, c, and e of Criminal Procedural Law (KUHAP). Secondly, the consideration of punishment severity sentenced by the Judge has been equivalent to the Defendant’s guilt and has fulflled the provision of Article 2 clause of Law Number 21 of 2007. In relation to Article 183 jo Article 193 clause (1) of Criminal Procedural Law (KUHAP), this Judge’s decision has been appropriate. Recalling that in sentencing the Defendant, the judge has considered at least two legal evidence and has obtain conviction that the defendant is evidently guilty legally for committing human traffcking crime and has been consistent with Article 193 clause (1) of Criminal Procedural Law (KUHAP).Keywords: Public Prosecutor’s authentication attempt, Judge’s rationale, human traffcking